Sleep alterations and iron deficiency anemia in infancy - Peirano, Patricio D. (2010)
Iron-deficiency anemia (IDA) continues to be the most common single nutrient deficiency in the world. An estimated 20-25% of the world’s infants have IDA, with at least as many having iron deficiency without anemia. Infants are at particular risk due to rapid growth and limited dietary sources of iron. We found that infants with IDA showed different motor activity patterning in all sleep-waking states and several differences in sleep states organization. Sleep alterations were still apparent years after correction of anemia with iron treatment in the absence of subsequent IDA. We suggest that altered sleep patterns may represent an underlying mechanism that interferes with optimal brain functioning during sleep and wakefulness in former IDA children.